Moderation Of Religiosity On The Determinants Of Individual Non-Employee Taxpayers' Perceptions Of Tax Avoidance Ethics - Wahyuni, Desak Ari Gita; Marfiana, Andri (WIM Solusi Prima, 2024)
This research aims to determine whether the religiosity variable can moderate the influence of the taxation system variables, discrimination, tax justice and understanding of taxation on the perception of non-employee individual taxpayers in Denpasar City. The research method used is a quantitative approach with SEM PLS analysis techniques. Data and information were obtained from primary data using questionnaires distributed at Denpasar Timur Tax Office and Denpasar Barat Tax Office. The results of data processing from 100 respondents consisting of non-employee taxpayers show that the tax system, discrimination, tax justice, understanding of taxation and religiosity can explain the variable perception of ethical tax avoidance by 62.5% while the remaining 37.5% is explained by variables outside this research. The results of hypothesis testing show that the variables of the tax system, discrimination, tax fairness and religiosity have a significant positive influence on the perception of the ethics of tax avoidance. Meanwhile, the tax understanding variable does not have a significant influence on tax avoidance ethics. The better the tax system, tax fairness and taxpayer religiosity, the higher the intention to avoid paying taxes. This increase in the intensity of tax evasion can occur due to several factors such as the complexity of regulations, legal permits, effective sanctions for tax violators, and different religious views. On the other hand, high levels of discrimination will make taxpayers think that tax avoidance is one way to fight or overcome the inequality produced by the system. The conclusion of this research is that the religiosity variable cannot moderate the four independent variables because the ethical values that arise related to religiosity cannot always play a role in how individuals deal with taxation.